A scheme for location-based Internet broadcasting and its applications. - Oh, Jongtaek (IEEE Communications magazine)
In this article, a new Internet broadcasting scheme that combines the existing network-wide unicast protocol and a subnet-wide broadcast protocol is proposed. The proposed broadcasting scheme is appropriate for location-based push services and requires only a minor functional addition to the existing edge routers, base stations, or access points. To eliminate unnecessary broadcasting traffic, an efficient terminal-originated triggering algorithm for broadcast initiation is introduced. The scheme provides location-based information to mobile users without the need for protocol reconfigurations or prior knowledge of a user's location. We also discuss some potential applications of the scheme. Performance of the proposed scheme has been evaluated and selected results are presented in this article. The evaluation shows that the broadcasting scheme significantly reduces the network traffic and the server load.